Elaboración y comercialización de papel artesanal con cartones de cubetas de huevos, revistas y periódicos - Del pozo Vera, Jipson javier (2018)
urrently in this globalized world and under a high level of economic, financial, and social uncertainties by various macroeconomic factors, countries in general seek to strengthen their economies and reduce the effects of the global and labor crisis, incorporating development, innovation and emergence efforts. business ideas known as entrepreneurship